Strategic Planning to Increase Farmers’ Income in Denpasar City - Dewi, Ni Ketut Sari (Journal of A Sustainable Global South; Vol 8 No 2 (2024): August 2024, 2024)
The phenomenon that happens in the administration of the city government is that there are still many farmers who depend on agricultural management, even though the city has very narrow land and the rate of land conversion is very high and massive. In order to increase farmers income through improved performance on the implementation of programs, activities, and sub-activities of the Denpasar City Agriculture Office in 2023 as stated in the Denpasar City Agriculture Office Strategic Plan for the 2021-2026 period (after review), one of which is the achievement of performance indicators with the target of increasing farmers income, in the form of Benefit Cost (B/C) ratio of income and costs of rice farming. The writing methodology includes data collection methods and data processing methods. The author analyzes the data in this Policy Paper by combining various analysis techniques as follows: Quantitative analysis using various instruments at the data processing stage to prepare the 2025 Work Plan Document of the Department of Agriculture; Analysis of causal relationships using logical frameworks and work tables. This technique is used to trace the relationship between one document and another, and; Analysis of performance achievements using a comparison between achievements and targets.